A Quasi-Experimental, Before-After Trial Examining the Impact of an Emergency Department Mechanical Ventilator Protocol on Clinical Outcomes and Lung-Protective Ventilation in Acute Respiratory Distress Syndrome. Issue 4 (April 2017) - Fuller, Brian M.; Ferguson, Ian T.; Mohr, Nicholas M.; Drewry, Anne M.; Palmer, Christopher; Wessman, Brian T.; Ablordeppey, Enyo; Keeperman, Jacob; Stephens, Robert J.; Briscoe, Cristopher C.; Kolomiets, Angelina A.; Hotchkiss, Richard S.; et al.
Abstract : Objectives: To evaluate the impact of an emergency department mechanical ventilation protocol on clinical outcomes and adherence to lung-protective ventilation in patients with acute respiratory distress syndrome. Design: Quasi-experimental, before-after trial. Setting: Emergency department and ICUs of an academic center. Patients: Mechanically ventilated emergency department patients experiencing acute respiratory distress syndrome while in the emergency department or after admission to the ICU. Interventions: An emergency department ventilator protocol which targeted variables in need of quality improvement, as identified by prior work: 1) lung-protective tidal volume, 2) appropriate setting of positive end-expiratory pressure, 3) oxygen weaning, and 4) head-of-bed elevation. Measurements and Main Results: A total of 229 patients (186 preintervention group, 43 intervention group) were studied. In the emergency department, the intervention was associated with significant changes ( p < 0.01 for all) in tidal volume, positive end-expiratory pressure, respiratory rate, oxygen administration, and head-of-bed elevation. There was a reduction in emergency department tidal volume from 8.1 mL/kg predicted body weight (7.0–9.1) to 6.4 mL/kg predicted body weight (6.1–6.7) and an increase in lung-protective ventilation from 11.1% to 61.5%, p value of less than 0.01. The intervention was associated with a reduction in mortality from 54.8% to 39.5% (odds ratio, 0.38; 95% CI, 0.17–0.83; p = 0.02) and a 3.9 day increase in ventilator-free days, p value equals to 0.01. Conclusions: This before-after study of mechanically ventilated patients with acute respiratory distress syndrome demonstrates that implementing a mechanical ventilator protocol in the emergency department is feasible and associated with improved clinical outcomes. Abstract : Supplemental Digital Content is available in the text.